The relationship between spirituality and quality of life of the elderly - Ganda Sigalingging; Magdalena Ginting; Paulina Yohana Siburian (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Various serious problems resulting from the lack of spiritual support for the elderly in nursing homes, particularly in mental health, impact their overall quality of life. Fulfilling spiritual support, as a value system that provides them with strength, hope, and meaning in life, as well as acceptance of the impact of aging, is crucial in maintaining inner peace, meaning in life, and the ability to adapt to the limitations of old age. Purpose: to analyze the relationship between spirituality and the quality of life of the elderlyMethod: This research is a descriptive correlational design using a cross-sectional approach. A population of 67 elderly people, a sample of 30 of whom were selected using purposive sampling techniques. The instruments used were the Daily Spirituality Scale (DSELS) and the modified World Health Organization Quality of Life Scale (WHOQOL-BRELF). Data analysis was conducted bivariately with a chi-square test at the confidence level (α = 0.05).Results: The results of the study showed that the majority of elderly people had a low level of spirituality (11 people) (40%) and a low quality of life (21 people) (70%). The chi-square test obtained a p-value of 0.023 (<0.05).Conclusion: It is necessary to provide guidance on routine spiritual activities, spiritual counseling sessions, and facilitate communication and visits from families. For the elderly, it is recommended to be more active in participating in activities organized by the foundation and to be proactive in establishing social and spiritual relationships, as an effort to improve the mental well-being and improve the quality of life of the elderly.